Assessing the relationship of prospective, retrospective, and everyday memory with cognitive failure among Bangladeshi adults - Bakul, Fariea; Roy, Mollika; Aktar , Sanjida; Karmaker, Chhanda (Dhaka University Journal of Biological Sciences, 2024)
Memory has a profound impact on every aspect of who we are. The present study explored the extent to which deficits in everyday memory (EM), prospective memory (PM), and retrospective memory (RM) serve as predictive indicators of cognitive failure (CF) in the context of the Bangladeshi population, as well as to identify differences for the variables across various age cohorts and genders. A total of 352 participants took part in the cross-sectional survey of PM, RM, EM, CF, and the demographic questionnaire package. The main goal of this study was accomplished by the findings, which showed a positive link between CF and EM, PM, and RM. Additionally, the results show that while deficiencies in RM have a somewhat smaller correlation with CF, lapses in EM and PM primarily serve as predictive indications of CF. The results of the current study reveal a recurrent pattern of memory recall and cognitive failure, where men are doing generally better than those of women. A noteworthy finding was the superior performance of middle-aged adults in comparison to their younger counterparts. Hence the majority of memory research is conducted on Western or European people, therefore the current study and its findings can serve as a strong starting point for determining the reasons, nature, and direction of the correlations between memory types and cognitive failures. Dhaka Univ. J. Biol. Sci. 33(1): 133-142, 2024 (January)